2021
DOI: 10.3389/fmicb.2021.655228
|View full text |Cite
|
Sign up to set email alerts
|

Host Adaptive Evolution of Avian-Origin H3N2 Canine Influenza Virus

Abstract: Since its first isolation in around 2007, the avian-origin H3N2 canine influenza virus (CIV) has become established and continues to circulate in dog populations. This virus serves as a useful model for deciphering the complex evolutionary process of interspecies transmission of influenza A virus (IAV) from one species to its subsequent circulation in another mammalian host. The present investigation is a comprehensive effort to identify and characterize genetic changes that accumulated in the avian-origin H3N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 68 publications
(109 reference statements)
1
4
0
Order By: Relevance
“…However, newly emerging strains show an increasing trend in CAI values for dogs [ 65 ]. Similar observations have been noted in influenza viruses such as H1N1/09 and canine influenza H3N2 [ 66 ]. The preference of ASFV for tick-like codon usage may result from prolonged co-evolution with soft ticks, and it is speculated that over time, an adaptation to pig codon usage, similar to the evolution observed in influenza viruses, may occur.…”
Section: Discussionsupporting
confidence: 87%
“…However, newly emerging strains show an increasing trend in CAI values for dogs [ 65 ]. Similar observations have been noted in influenza viruses such as H1N1/09 and canine influenza H3N2 [ 66 ]. The preference of ASFV for tick-like codon usage may result from prolonged co-evolution with soft ticks, and it is speculated that over time, an adaptation to pig codon usage, similar to the evolution observed in influenza viruses, may occur.…”
Section: Discussionsupporting
confidence: 87%
“…Another possibility is that the number of sequences used to calculate was relatively small, as only limited sequences have been isolated from canine and equine viruses. Besides, in another similar study, 54 characterized genetic substitutions were found to be accumulated and fixed in H3N2 CIV during its circulation in dogs ( 39 ). However, there were only five markers observed in our study.…”
Section: Discussionmentioning
confidence: 94%
“…H3N2 CIV was first reported in Korea in 2007. Subsequently, H3N2 CIV was also reported in China by our laboratory, indicating that this virus was circulating in the Chinese dogs in 2006 (6,7).…”
Section: Introductionmentioning
confidence: 79%